The influence of short-term fixture congestion on position specific match running performance and external loading patterns in English professional soccer - Jones, R. N.; Greig, M.; Mawéné, Y.; Barrow, J.; Page, R. M. (Journal of Sports Sciences, 2019)
The aim of the current study was to investigate positional specific physical performance and external load responses to short term fixture congestion in English professional soccer. A total of 515 match observations were categorised as G1: the first game in a week with >4 days following a previous game, G2: the second game in a week played <4 days since G1, and G3: the third game in a week played with <4 days between each of the previous games. Global positioning system and accelerometer-based metrics were partitioned into fifteen-minute epochs. These data were then analysed using a linear mixed model to assess both the within and between game positional differences. Total, low-intensity (<4.0 m/s), medium-intensity (MID; 4.0-5.5 m/s), and sprint distance (>7.0 m/s) were significantly different across games. No between game positional differences were identified; however, within match position specific differences were observed for measures of MID and HID. No significant differences were evident for accelerometer derived metrics between games or across positions. The current data suggests that the use of fifteen minute within game epochs enables the detection of alterations in physical output during congested schedules. The observed within game positional differences has implications for player specific conditioning and squad rotation strategies.